2017
DOI: 10.1080/14756366.2017.1419218
|View full text |Cite
|
Sign up to set email alerts
|

Bulge oligonucleotide as an inhibitory agent of bacterial topoisomerase I

Abstract: Bacterial topoisomerase I (Btopo I) was defined as potential target for discovery of new antibacterial compounds. Various oligonucleotides containing bulge structure were designed and synthesised as inhibitors to Btopo I in this investigation. The results of this study demonstrated that the designed oligonucleotides display high inhibitory efficiency on the activity of Btopo I and the inhibitory effect could be modulated by the amount of bulge DNA bases. The most efficient one among them showed an IC50 value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…The first step in the catalytic cycle of the enzyme is the recognition of the single-stranded regions in duplex DNA [ 139 ]. A series of 84 bp double-stranded oligonucleotides with variations in the number of bulge bases in a single-stranded loop were synthesized and tested for inhibition of the relaxation activity of E. coli topoisomerase I [ 140 ]. Inhibition efficiency improves as the size of the single-stranded loop increases from 1 to 10 base in length with IC 50 reaching 63.1 nM.…”
Section: Recent Attempts To Discover Novel Bacterial Topoisomerasementioning
confidence: 99%
See 2 more Smart Citations
“…The first step in the catalytic cycle of the enzyme is the recognition of the single-stranded regions in duplex DNA [ 139 ]. A series of 84 bp double-stranded oligonucleotides with variations in the number of bulge bases in a single-stranded loop were synthesized and tested for inhibition of the relaxation activity of E. coli topoisomerase I [ 140 ]. Inhibition efficiency improves as the size of the single-stranded loop increases from 1 to 10 base in length with IC 50 reaching 63.1 nM.…”
Section: Recent Attempts To Discover Novel Bacterial Topoisomerasementioning
confidence: 99%
“…Inhibition of eukaryotic calf thymus topoisomerase I relaxation activity was not observed. It was hypothesized that because the single-stranded loops in the bulge oligonucleotides are not base-paired, the bulge oligonucleotides may be acting as irreversible competitive inhibitors [ 140 ].…”
Section: Recent Attempts To Discover Novel Bacterial Topoisomerasementioning
confidence: 99%
See 1 more Smart Citation
“…Yang and coworkers reported that linear oligonucleotides containing mismatch or bulge can act as the irreversible inhibitors of bacterial topoisomerase I [66,67], but no direct evidence such as the formation of covalent complex between DNA and proteins was provided in their studies. In our recent studies, particularly designed small DNA circles with high bending stress were synthesized [68].…”
Section: Topoisomerase Inhibitorsmentioning
confidence: 99%
“…Ñêîíñòðóèðîâàííûå îëèãîíóêëåîòèäû ñ õàðàêòåðíîé ïåòëåé â ñòðóêòóðå ïðèâîäÿò ê íåîáðàòèìûì ïîâðåaeäåíèÿì áàêòåðèàëüíîé Topo I áåç êàêèõ-ëèáî ýôôåêòîâ â îòíîøåíèè ýóêàðèîòè÷åñêîé òîïîèçîìåðàçû I. Ïðîáëåìà ïðîäâèaeåíèÿ ìîëåêóëû â êëèíè÷åñêóþ ïðàêòèêó ñâÿçàíà ñ ïëîõîé ïðîíèöàåìîñòüþ âíóòðü áàêòåðèàëüíîé êëåòêè, èññëåäîâàòåëè âîçëàãàþò íàäåaeäû íà íàíîòåõíîëîãèè è ôàðìàöåâòè÷åñêèå ïîäõîäû [54].…”
Section: ôåðìåíòû òîïîèçîìåðàçà I òèïàunclassified